Ice Shelf Water and marine ice production in the frontal zone of Hells Gate Ice Shelf (Terra Nova Bay, Antarctica): implications on mass balance - Tison, Jean-Louis; Barbante, Carlo; Lorrain, Reginald; Bondesan, A.; Stievenart, Michel (1995)
info:eu-repo/semantics/nonPublished